2021
DOI: 10.1111/ele.13951
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits explain the consistent resistance of biodiversity to plant invasion under nitrogen enrichment

Abstract: Elton's biotic resistance hypothesis, which posits that diverse communities should be more resistant to biological invasions, has received considerable experimental support. However, it remains unclear whether such a negative diversity–invasibility relationship would persist under anthropogenic environmental change. By using the common ragweed (Ambrosia artemisiifolia) as a model invader, our 4‐year grassland experiment demonstrated consistently negative relationships between resident species diversity and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 70 publications
3
29
0
1
Order By: Relevance
“…Furthermore, the effects of different abiotic and biotic variables on soil P bioavailability were quantified by the LMMs (Li et al, 2022;Rao et al, 2021). Before doing that, in order to avoid multicollinearity, we used a variance inflation factor (VIF) threshold of 3.3 to eliminate those variables which were strongly correlated (Fanin et al, 2020;Kock, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the effects of different abiotic and biotic variables on soil P bioavailability were quantified by the LMMs (Li et al, 2022;Rao et al, 2021). Before doing that, in order to avoid multicollinearity, we used a variance inflation factor (VIF) threshold of 3.3 to eliminate those variables which were strongly correlated (Fanin et al, 2020;Kock, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To detect the significant differences between agro‐ and natural ecosystems across China in total soil P, bioavailable soil P and the relative abundances of P cycling genes (Table S3), we performed the linear mixed‐effects model (LMM) analysis using lmerTest package (Kuznetsova et al, 2017) with study site identity as a random effect. Furthermore, the effects of different abiotic and biotic variables on soil P bioavailability were quantified by the LMMs (Li et al, 2022; Rao et al, 2021). Before doing that, in order to avoid multicollinearity, we used a variance inflation factor (VIF) threshold of 3.3 to eliminate those variables which were strongly correlated (Fanin et al, 2020; Kock, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical and experimental studies that considered small spatial scales frequently find a negative relationship between native diversity and invasibility in different ecosystems (Gazol et al, 2013; Kennedy et al, 2002; Levine, 2000; van Ruijven et al, 2003). For example, diverse native communities were less heavily invaded compared to less diverse native communities, even when the resource availability increased, indicating the robustness of biotic resistance (Li et al, 2021; Maron & Marler, 2007). However, observational field studies found that, particularly at larger spatial scales, habitats of high native diversity were more heavily invaded than habitats of low native diversity, suggesting a so‐called ‘the rich get richer pattern’ (Jauni & Hyvonen, 2012; Peng et al, 2019; Stohlgren et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the number of dimensions of community-level leaf traits, we performed a principal component analysis (PCA) on the five traits and used the first principal component (PC1, see Figure S1 ), which accounted for 98.27% of the total variation in the data, in the ensuing analyses of structural equation modeling involving community-level leaf traits. We then calculated the community-weighted mean trait values (FunTra) of PC1, weighted by the relative aboveground biomass of each dominant species in the community ( Li et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%